Bank credit and trade credit: Evidence from natural experiments - Chen, Shenglan; Ma, Hui; Wu, Qiang (Journal of Banking & Finance, 2019)
Prior studies find mixed evidence about the substitution relation between bank credit and trade credit. In this paper, using two bank interest rate deregulations in China, we revisit the substitution hypothesis by examining how exogenous increases in the availability of bank credit affect trade credit. We find that firms with higher credit risk increased their use of bank credit and reduced their use of trade credit after the 2004 bank interest rate ceiling deregulation, whereas firms with lower credit risk increased their use of bank credit and reduced their use of trade credit after the 2013 bank interest rate floor deregulation. Our results provide supportive evidence for the substitution hypothesis that firms reduce their use of trade credit after the relaxation of bank credit and suggest that bank credit is more favorable short-term financing than trade credit.